Trust, information asymmetry and professional service online referral agents. Issue 6 (4th October 2017) - Pedeliento, Giuseppe; Andreini, Daniela; Bergamaschi, Mara; Klobas, Jane Elizabeth
Abstract : Purpose: The purpose of this paper is to evaluate how the intermediation of an online agent in the relationship between prospective clients and professional service providers affects individual purchasing processes and decisions, and satisfaction with the professional service provider once the commercial transaction is concluded. Design/methodology/approach: Drawing on the integrated trust-technology acceptance model, modified to include two additional variables to take into account of the specificities of the context investigated – users' perceived reduction of information asymmetry and satisfaction with the professional service provider – a research framework is developed and tested with a research design combining a decision tree procedure with structural equation modelling and multi-group analysis. Participants are 188 users of an Italian website which incorporates an online agent that refers notaries to prospective clients. Findings: Decisions to purchase professional services brokered by online agents depend upon trust in the agent, and users' perceptions of the agent's ability to reduce information asymmetry, as well as its perceived usefulness. Online agents for professional services can be effective as well as efficient: users who bought the service from an agent-referred notary had higher levels of satisfaction with their professional service provider than users who purchased the service from a different notary. Originality/value: This is the first empirical effort to investigate the effects of online agents in the specific context of professional service purchasing. The uniqueness of the research context permitted identification of a new type of online agent, the "double-sided online referral agent".